The Double-Edged Sword of Charismatic Leaders: Does The Current Organization Still Need Them? - Masyhuri, Muhammad (Departemen Manajemen Fakultas Ekonomi dan Bisnis Universitas Negeri Malang, 2022)
The concepts of charisma and charismatic leaders become the attention of many scholars from various academic disciplines and become a controversial topic due to the double-edge impacts, especially in today’s world when the use of Internet of Things (IoT) is widespread through social media.. It leads to some questions: 1) do today's businesses and organizations still need a charismatic leader? 2) What are the best practices and traits that charismatic leaders should adopt in today's organization?This paper reviewed these types of leaders and explained the organizational and business roles, the best practices, and the qualities of such leaders. This paper also explained both the advantages and disadvantages of charismatic leaders. The researchers reviewed the best practices and qualities of charismatic leaders based on relevant publications and examples from scholars. The researchers recommended future field research reveal the correlation between charismatic leaders and young audiences in this